Síntese e caracterização da peneira molecular MCM-41 contendo terras raras na dessulfurização, utilizando tiofeno como molécula sonda - Alves, José Antônio Barros Leal Reis (2010)
Mesoporous molecular sieves of MCM-41 type are considered as promising support for metal in the refining processes of petroleum-based materials as catalysts and adsorbents for environmental protection. In this work, mesoporous molecular sieves MCM-41 were modified with different rare earth ions (La, Eu e Yb) for the obtaining nanostrutured materials with catalytic properties. The catalysts were synthesized by the hydrothermal method at 100oC for 120 h, presenting, all the samples, in the gel of synthesis molar ratio Si/Ln = 50. The obtained materials after calcination at 500oC for 2 h were characterized by XRD, surface area BET, TG/DTG, FTIR, and hydrothermal stability at 700ºC. The XRD analysis of the catalysts indicated that the materials containing rare earth presented characteristic hexagonal structure of the mesoporous materials of the type MCM-41. The TG curves showed that the decomposition of the structural template occurs in the materials at temperatures lower than 500oC. The samples presented variations as the specific superficial area, average diameter of pores and thickness of the silica wall, as a function of the nature of the rare earth impregnated in the mesoporous material. Hydrotermal stability was evaluated through the exposition of the materials to water vapour at 700°C. The thiophene adsorptions reach a maximum at 80% of conversion and incorporation of the rare earths showed influence in the process. Adsorption capacity followed the sequence: Yb-MCM-41 < La-MCM-41 < Eu-MCM-41 < MCM-41